Implementation Of Cigarette Tax Earmaking Policy In The Regional Tax And Level Management Agency Of North Sumatra Province - Tri Kurniati; Juliana Nasution (Jurnal Riset Perpajakan: Amnesty, 2022)
Tax is one of the state revenues. Based on Tax Law No. 23 of 2019 concerning the management of National resources, cigarette taxes are considered regional taxes under the auspices of the Ministry of Finance of the Republic of Indonesia. The cigarette tax imposed at 10% of cigarette excise is also intended to optimize the allocation of revenue-sharing funds for cigarette taxes for public health in collaboration with BPJS by 37.5%. The purpose of this study was to determine the implementation of the cigarette tax earmaking tax policy at the Regional Tax and Levy Management Agency of North Sumatra Province. This study uses a descriptive qualitative type, the research is carried out by collecting and filtering detailed information to be grouped into important things, then describing and drawing conclusions on the picture obtained. The results of this study indicate that the Regional Tax and Levy Management Agency for the North Sumatra Province has determined the allocation of funds in accordance with Law no. 28 of 2009 which is at least 50% to fund public health services. In the implementation of distribution, the Provincial Government submits data on Cigarette Tax deductions that are deposited with BPJS Health AS part of the obligations of the Health Insurance program